2017
DOI: 10.1016/j.mce.2016.11.011
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin suppresses adipogenesis through both AMP-activated protein kinase (AMPK)-dependent and AMPK-independent mechanisms

Abstract: People with Type 2 diabetes mellitus (T2DM) have reduced bone mineral density and an increased risk of fractures due to altered mesenchymal stem cell (MSC) differentiation in the bone marrow. This leads to a shift in the balance of differentiation away from bone formation (osteogenesis) in favour of fat cell development (adipogenesis). The commonly used anti-diabetic drug, metformin, activates the osteogenic transcription factor Runt-related transcription factor 2 (Runx2), which may suppress adipogenesis, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 54 publications
3
75
0
Order By: Relevance
“…In vitro, metformin also appears to protect against AGE‐induced cellular injury and cell death in osteoblastic cells, similar to described effects in other human and rodent complication‐affiliated cell types such as neurons, macrophages, cardiomyocytes, and renal tubular cells . In many cases, these effects are thought to be mediated by metformin activation of AMPK signaling pathways . Given that AMPK is a regulator of cellular energy sensing, a role for metformin in stimulating osteogenesis and inhibiting adipogenesis is conceptually consistent with its presumed systemic effects .…”
Section: Drugs and Bonesupporting
confidence: 55%
See 1 more Smart Citation
“…In vitro, metformin also appears to protect against AGE‐induced cellular injury and cell death in osteoblastic cells, similar to described effects in other human and rodent complication‐affiliated cell types such as neurons, macrophages, cardiomyocytes, and renal tubular cells . In many cases, these effects are thought to be mediated by metformin activation of AMPK signaling pathways . Given that AMPK is a regulator of cellular energy sensing, a role for metformin in stimulating osteogenesis and inhibiting adipogenesis is conceptually consistent with its presumed systemic effects .…”
Section: Drugs and Bonesupporting
confidence: 55%
“…Examining both murine and human‐derived mesenchymal stem cell cultures, metformin exposure has been shown in several studies to induce an overall shift in mesenchymal stem cell differentiation toward the osteogenic pathway and away from adipogenesis . Further evidence of the osteogenic potential of metformin comes from studies utilizing a variety of osteoblast‐specific cell cultures, including UMR106 cells, MC3T3‐E1 cells, primary mouse calvarial cultures, and primary rat osteoblast cultures.…”
Section: Drugs and Bonementioning
confidence: 99%
“…Metformin (MET) has been used as the first‐line drug therapy for T2DM, due to its excellent inhibitory effect on hepatic glucose production . Berberine (BB) is an isoquinoline alkaloid originally isolated from Chinese herb Coptis chinensis (Huang lian), which exerts anti‐diabetic and anti‐inflammatory activities .…”
Section: Introductionmentioning
confidence: 99%
“…The results are supported by previous studies in 3 T3‐L1 adipocytes (Jiang et al, , ; Li et al, ). On the contrary, recent conflicting reports involving the role of AMPK in adipogenesis showed that suppressing AMPK activity with compound C, a specific AMPK inhibitor, resulted in a decreased lipid accumulation and protein level of the adipogenic marker gene Perilipin a in adipogenic‐induced C3H10T1/2 mouse mesenchymal stem cells (MSC) (Chen et al, ). Moreover, knockout of Ampka in mouse embryonal fibroblasts (MEF) downregulated the expression of C/EBPβ protein and repressed adipogenic differentiation of the cells (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, recent conflicting reports involving the role of AMPK in adipogenesis showed that suppressing AMPK activity with compound C, a specific AMPK inhibitor, resulted in a decreased lipid accumulation and protein level of the adipogenic marker gene Perilipin a in adipogenic‐induced C3H10T1/2 mouse mesenchymal stem cells (MSC) (Chen et al, ). Moreover, knockout of Ampka in mouse embryonal fibroblasts (MEF) downregulated the expression of C/EBPβ protein and repressed adipogenic differentiation of the cells (Chen et al, ). Furthermore, adipose tissue‐specific knockout of Ampka1 or Ampka2 in mice lead to an increased lipolysis and reduced triacylglycerol (TAG) content in adipocytes; meanwhile, the mice were lean (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%